Maximum Power Point Tracking Control of Direct Methanol Fuel Cell - Zhang Mingbo; Yan Ting; Gu Jinguang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The performance of direct methanol fuel cell (DMFC) is closely related to its operating conditions, and there exists a specific combination of operating conditions at which the DMFC output maximum power to the driven load. Working at maximum power point (MPP) can lower the methanol crossover and ancillary power consumption so as to improve the global efficiency of the system. The fuzzy controller proposed in this paper provides a simple and robust way to keep the DMFC working at MPP by adjusting the operating conditions followed by the variation of driven load in real time. Simulation shows that the fuzzy control approach can yield satisfactory results. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3657